Restauro e innovazione al Palazzo Ducale di Mantova: la stampa 3D al servizio dei Gonzaga - Bigliardi, Giulio; Dioni, Pietro; Panico, Giovanni (Archeomatica, 2015)
Time Compression Technologies are widely used in the design industry to support product innovation and improve competitiveness. Thanks to their transversal characteristics and flexibility, they can be applied with sucess in the field of Cultural Heritage for planning new methods, in particular the technology of 3D scanning and 3D printing. This paper wants to show a concrete example of the application of these technologies in a restoration works in Palazzo Ducale in Mantova, for the reconstruction of an architectural frame of the sixteenth century.